Exploring High-Symmetry Lanthanide-Functionalized Polyoxopalladates as Building Blocks for Quantum Computing - José J. Baldoví; Aleksandar Kondinski (Inorganics, 2018)
The structural, electronic, and magnetochemical properties of the star-shaped polyoxopalladate [Pd15O10(SeO3)10]10− (POPd) and its lanthanide-functionalized derivatives have been investigated on the basis of density functional theory, followed by a ligand field analysis using the Radial Effective Charge (REC) model. Our study predicts that heteroPOPd is a robust cryptand that enforces D5h symmetry around the encapsulated Ln3+ centers. This rigid coordination environment favors an interesting potential magnetic behavior in the Er and Ho derivatives, and the presence of a cavity in the structure suggests an effective insulation of the electronic system from the lattice phonons, which may be of interest for molecular spintronics and quantum computing applications.